2013
DOI: 10.1007/s10648-013-9219-1
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Performance: A Motivational Experiences Model of Stereotype Threat

Abstract: The contributing role of stereotype threat (ST) to learning and performance decrements for stigmatized students in highly evaluative situations has been vastly documented and is now widely known by educators and policy makers. However, recent research illustrates that underrepresented and stigmatized students’ academic and career motivations are influenced by ST more broadly, particularly through influences on achievement orientations, sense of belonging, and intrinsic motivation. Such a focus moves conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 197 publications
3
82
0
3
Order By: Relevance
“…Further research should contribute to a greater understanding of the conditions under which and the strategies with which scaffolding leads to strong learning outcomes. Future research should also investigate how to extend scaffolding's reach to benefit underrepresented groups in STEM, a very important goal (Ceci, Williams, & Barnett, 2009;Syed, Azmitia, & Cooper, 2011;Thoman, Smith, Brown, Chase, & Lee, 2013). This could be pursued through a combination of strategies: look at the differences between scaffolds that work well among underrepresented groups, and those that are not as effective, examine the literature on designing effective instructional supports for members of underrepresented groups (Cuevas, Fiore, & Oser, 2002;Marra, Peterson, & Britsch, 2008), examine the literature on universal design for learning (Rao, Ok, & Bryant, 2014;Scott, Mcguire, & Shaw, 2003), and examine whether there are differences in how students from underrepresented groups are using scaffolds that could explain lower effectiveness (Belland & Drake, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Further research should contribute to a greater understanding of the conditions under which and the strategies with which scaffolding leads to strong learning outcomes. Future research should also investigate how to extend scaffolding's reach to benefit underrepresented groups in STEM, a very important goal (Ceci, Williams, & Barnett, 2009;Syed, Azmitia, & Cooper, 2011;Thoman, Smith, Brown, Chase, & Lee, 2013). This could be pursued through a combination of strategies: look at the differences between scaffolds that work well among underrepresented groups, and those that are not as effective, examine the literature on designing effective instructional supports for members of underrepresented groups (Cuevas, Fiore, & Oser, 2002;Marra, Peterson, & Britsch, 2008), examine the literature on universal design for learning (Rao, Ok, & Bryant, 2014;Scott, Mcguire, & Shaw, 2003), and examine whether there are differences in how students from underrepresented groups are using scaffolds that could explain lower effectiveness (Belland & Drake, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This is concerning, as it is very important to maximize success opportunities in STEM for students from underrepresented groups (Ceci, Williams, & Barnett, 2009;National Research Council, 2011;Thoman, Smith, Brown, Chase, & Lee, 2013). Further research is needed to examine how to design and deploy computer-based scaffolding so as to increase its efficacy among underrepresented groups.…”
Section: Results From the Meta-analysismentioning
confidence: 99%
“…However, repeated exposure to social identity threat can push people to withdraw from a career path, despite interest in it (Thoman et al 2013;Woodcock et al 2012). In a study of gender minorities in higher education, Steele et al (2002) found that women in majors dominated by men experienced higher levels of social identity threats than other students and were more likely to think about changing their major as compared to others.…”
Section: Interest and Self-efficacymentioning
confidence: 99%